SISTEM PENUNJANG KEPUTUSAN PADA RESERVASI WEDDING MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Prasetyo, Muhamad Awiet Wiedanto (DoubleClick: Journal of Computer and Information Technology, 2021)
Umah penganten is a wedding organizer serving in the service sector providing equipment for wedding events established since 2014. Umah pengantin is located in Situwangi RT 04 RW 04, Rakit, Banjarnegara area.  At Umah pengantin, in the process of choosing a wedding package, often find customers who are confused in determining the wedding package because of limited information about the package, the number of criteria offered.  With this, the purpose of this study is to design and create a decision support system for recommendation of wedding packages to the bride and groom.  This system uses the Simple Additive Weighting (SAW) method as its ranking weighting method.  With the development model using the Extreme Programming (XP) system.  The result of this research is the decision support system for the wedding package recommendation wasmade